Artificial Intelligence Disclosure as a Strategic Signal: Implications for Corporate Financial Performance - Lina Kurniati Ningsih; Siti Jubaedah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study examines Artificial Intelligence Disclosure as a strategic non-financial signal and its implications for the financial performance of banking companies listed on the Indonesia Stock Exchange during 2021–2024. Financial performance is measured using Return on Assets, Return on Equity, Net Interest Margin, and Price to Earnings. This study applies a quantitative approach using secondary data obtained from annual reports and financial statements. Using purposive sampling, 47 banking companies were selected, resulting in 188 firm-year observations. The data were analyzed using panel data regression with model selection through the Chow, Hausman, and Lagrange Multiplier tests. The findings show that Artificial Intelligence Disclosure has no significant effect on Return on Assets and Return on Equity, but has a positive and significant effect on Net Interest Margin and Price to Earnings. These results indicate that Artificial Intelligence Disclosure is more strongly reflected in operational efficiency and market valuation than in short-term accounting profitability. This study contributes to the development of signaling theory by positioning Artificial Intelligence Disclosure as a technology-based strategic signal. Practically, the findings imply that banking management should strengthen transparent and informative Artificial Intelligence Disclosure to enhance investor confidence and competitiveness in the digital transformation era.